Efficacy and safety of transarterial chemoembolization plus sorafenib in patients with recurrent hepatocellular carcinoma after liver transplantation - Zhang, Xia; Cai, Lirong; Fang, Jian; Chen, Fengsui; Pan, Fan; Zhang, Kun; Huang, Qian; Huang, Yuju; Li, Dongliang; Lv, Lizhi; Chen, Man; Yan, Ruiying; et al. (Frontiers in Oncology, 2023)
Objectives: To explore the benefit and safety of transarterial chemoembolization (TACE) in combination with sorafenib in patients with recurrent hepatocellular carcinoma (HCC) after orthotopic liver transplantation (OLT). Methods: In this multi-center retrospective study, 106 patients with recurrent HCC after OLT were included. Fifty-two patients were treated with TACE plus sorafenib (TS group) and 54 were treated with TACE alone (TC group). Primary and secondary endpoints including overall survival (OS) and progression-free survival (PFS), and safety were assessed. Results: The median OS (17 vs 10 months, P=0.035) and PFS (12 vs 6 months, P=0.004) in the TS group were longer than those in the TC group. On multivariate analysis, BCLC stage (HR [hazard ratio]=0.73 [95% CI, 0.27–0.99], P=0.036) and sorafenib medication (HR=2.26 [95% CI, 1.35–3.69], P=0.01) were identified as independent prognostic risk factors for OS. No severe adverse events related to sorafenib were noted in the TS group. Four patients discontinued sorafenib due to intolerance. Conclusion: TACE in combination with sorafenib is a feasible regimen to improve the survival with mild toxicity in patients with recurrent HCC after OLT.